Evaluation of parking space efficiency and sustainable land management strategies at Puri Raharja General Hospital in Denpasar - Indrashwara, Decky Cipta; Putri, Dewa Ayu Putu Adhiya Garini; Wedagama, Dewa Ayu Trisna Adhiswari; Tapa, I Gede Fery Surya; Kumara, I Nyoman Indra (Priviet Social Sciences Journal, 2025)
Puri Raharja General Hospital, one of the primary healthcare facilities in Denpasar City, faces challenges related to insufficient parking. This study investigates the parking characteristics and requirements to support the planning of a multilevel parking facility as an alternative solution for optimizing limited parking areas. Data were collected through parking inventories, cordon, and patrol surveys. The analysis revealed the following characteristics for light vehicles and motorcycles in both on-street and off-street parking areas: total parking volumes of 326 light vehicles and 1,646 motorcycles; peak accumulations of 37 and 252 vehicles per hour; average parking durations ranging from 1.034–3.484 hours and 1.289–3.250 hours; peak duration distributions of 74.60% and 77.18%; turnover rates of 0.650 and 1.236 vehicles per parking space unit (PSU) per hour; maximum parking capacities of 18 and 74 PSUs per hour; parking provisions of 265 light vehicles and 1,071 motorcycles; and parking indices of 2.891 and 8.782, respectively. Based on these findings, the total parking area requirements are estimated at 1,090.63 m² for light vehicles and 1,517.89 m² for motorcycles. The proposed construction of a motorcycle parking building on the south side of the hospital and redesign of off-street parking parallel to Gadung Street are expected to reduce the motorcycle parking demand to approximately 1,127.89 m².